Comparison of Biocompatibility of 3D-Printed Ceramic and Titanium in Micropig Ankle Hemiarthroplasty - Si-Wook Lee; Donghyun Lee; Junsik Kim; Sanghyun An; Chul-Hyun Park; Jung-Min Lee; Chang-Jin Yon; Yu-Ran Heo (Biomedicines)
Background: Ankle arthritis is a common degenerative disease that progresses as cartilage damage in the lower tibia and upper talus progresses, resulting in loss of joint function. In addition to typical arthritis, there is also structural bone loss in the talus due to diseases such as talar avascular necrosis. Total talus replacement surgery is the procedure of choice in end-stage ankle arthritis and consists of a tibial, talar component and an insert. However, in cases of severe cartilage and bone damage to the talar bone with less damage to the tibial cartilage, a talar component hemiarthroplasty may be considered. Although the application of total talus replacement surgery using ceramics has been studied, reports on the application of metal 3D printing technology are limited. We aimed to investigate the feasibility of partial talar components using ceramic and titanium 3D printing technology in terms of biocompatibility and stability through animal experiments. Methods: Preoperative 3D CT was acquired and converted to STL files to fabricate a partial talus component for ankle hemiarthroplasty using ceramic and titanium. Six minipigs with an average age of 17 months were implanted with three ceramic (C-group) and three titanium talar components (T-group) in the hind limb ankle joint. The surgery was performed under anesthesia in a sterile operating room and was performed by two experienced foot and ankle specialist orthopedic surgeons. Blood analysis and CT were performed before surgery and every month for 3 months after surgery to assess the extent of inflammatory response and physical stability, sacrifices were performed 3 months after surgery, and H&E staining and micro-CT analysis were performed to compare histological biocompatibility. A grading score was calculated to semi-quantitative assess and compare the two groups. Results: In the postsurgical evaluation, blood analysis revealed that both groups had increased white blood cell counts on the postoperative day after surgery. The white blood cell count increased more in the titanium group (1.85-fold) than in the ceramic group (1.45-fold). After 3 months, all values normalized. During the study, CT analysis confirmed that all artificial samples were displaced from their initial positions. In micro-CT analysis, the adhesive tissue score of the ceramic artificial sample was better than that of the titanium sample (average threshold = 3027.18 ± 405.92). In histologic and grading scores for the inflammatory reactions, the average inflammation indices of the ceramic and titanium groups were 2.0 and 1.21, respectively. Also, the average grade score confirmed based on the results of fibrous tissue proliferation and new blood vessels was 18.4 in the ceramic application group and 12.3 in the titanium application group. Conclusions: In conclusion, both titanium and ceramics have excellent biocompatibility for artificial joints, and ceramic materials can be used as novel artificial joints. Further research on the strength and availability of these ceramics is required.